An examination of the role faculty at one community college perceive they have in creating, growing and maintaining a Learning College culture - Jenkins, Sylvia, author; Davies, Timothy Gray, advisor (Colorado State University. Libraries, 2008)
Community colleges were created to help fill the void in American higher education faced by many and provide a skilled workforce to meet the needs of industry through an open door admissions policy. This open door policy and the easy access to a community college has generated increasing enrollments of students at all levels of preparedness. One major challenge community college leaders face is fulfilling the college's mission and at the same time realizing that students have many challenges that may prevent them from being successful. College leaders are looking for ways to create learning environments focused on student learning and student success. One model is called the Learning College. In the Learning College all constituents are considered learners and all college resources are directed to programs and services which effect learning. The participants and site of this study are all anonymous therefore I have used pseudonyms to protect their identity. However, it is possible that persons familiar with the college may have some recollection of the information shared. The leadership at Flatland Community College (FCC) realized there was a need to create a campus culture that was more focused on the learner and implement methods to determine if students were learning. They chose to adopt the Learning College as the model and the re-accreditation process, Academic Quality and Improvement Process (AQIP) as the framework for change. Organizational change theorist state change in an organization occurs when all constituent groups participate in the change process. In community colleges faculty are considered an influential constituent group and are critical to any transformation process. This case study examines the role faculty at FCC perceive they have in creating, growing, and maintaining a learning-centered college. Faculty participants have shared their level of knowledge in regards to the college's mission and direction. The participants shared their understanding of the Learning College, the Learning College Principles and why a transformation should occur and their role in the change process. In the final chapter are my recommendations to community college leaders who may be considering using the Learning College model as a mechanism for change.
Keywords: community college; faculty; learning college; community college education; school faculty; perceptions; culture